Vanadium-chromium precursor alloy for hydrogen storage and preparation method thereof

By preparing vanadium-chromium precursor alloys through aluminothermic reduction and three-phase electric arc furnace refining, the problems of high cost and complex process of vanadium-based hydrogen storage alloys have been solved. This has enabled the low-cost preparation of high-purity vanadium-chromium precursors, meeting the composition requirements of hydrogen storage alloys and improving the performance and stability of the alloys.

CN121183154APending Publication Date: 2025-12-23PANGANG GROUP VANADIUM & TITANIUM RESOURCES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511373858.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-12-23

AI Technical Summary

Technical Problem

Existing vanadium-based hydrogen storage alloys have high preparation costs, and research on vanadium-chromium precursor hydrogen storage materials is still in its early stages. The strong affinity between vanadium and hydrogen leads to the formation of stable hydrides from excess vanadium, which hinders hydrogen release and results in a highly complex preparation process.

Method used

Vanadium-chromium precursor alloys were directly prepared from vanadium pentoxide and chromium trioxide by aluminothermic reduction. The aluminothermic reduction formula and process were optimized to control the amount of hydrogen absorbed and the reversibility of hydrogen absorption and desorption, and to reduce the oxygen and impurity content. High-purity vanadium-chromium precursor alloys were obtained by refining in a three-phase electric arc furnace and water quenching.

Benefits of technology

This study enables the low-cost preparation of high-purity vanadium-chromium precursor alloys, meeting the compositional requirements of hydrogen storage alloys, reducing production costs, improving resource utilization, and enhancing alloy performance and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121183154A_ABST
    Figure CN121183154A_ABST
Patent Text Reader

Abstract

The invention relates to the field of metallurgy, and provides a vanadium-chromium precursor alloy for hydrogen storage and a preparation method thereof.The method comprises the steps that vanadium pentoxide, chromium sesquioxide, aluminum particles and a slag former are mixed to obtain a mixed furnace burden; the mixed furnace burden is put into a furnace body to be smelted in advance, ignition smelting and electrified refining are carried out, and an alloy cake is obtained; and putting the alloy cake into a water tank for water quenching, soaking for a preset time, and then crushing and screening to obtain the vanadium-chromium precursor alloy. According to the method, the aluminothermic reduction formula and process are deeply optimized, and the high-quality vanadium-chromium alloy is directly prepared from the oxide. The oxygen content and the impurity level in the alloy can be effectively reduced, the alloy purity is remarkably improved, accurate regulation and control of vanadium and chromium components can be achieved, the subsequent hydrogen storage alloy synthesis requirement is met, rich slag generated after refining can be returned to the technological process to be reused, the resource utilization rate is greatly increased, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of metallurgy, and more particularly to a vanadium-chromium precursor alloy for hydrogen storage and a preparation method thereof. BACKGROUND

[0002] Solid-state hydrogen storage technology is expected to make up for the safety problems and infrastructure construction difficulties caused by current high-pressure hydrogen storage technology. Vanadium-based hydrogen storage alloy developed based on the advantage of vanadium-titanium resources is currently the most optimal and cost-effective hydrogen storage material at room temperature, and has great application prospects. Currently, vanadium-based hydrogen storage alloy is mainly prepared by smelting with expensive vanadium as raw material, which has extremely high cost and seriously restricts the commercial application and promotion of vanadium-based hydrogen storage alloy.

[0003] The prior art discloses a method for treating vanadium-titanium-based hydrogen storage alloy by adopting low-temperature hydrogen absorption, which increases the brittleness of the vanadium-titanium-based hydrogen storage alloy, can efficiently and in large quantities prepare hydrogen storage alloy powder, and can finely control the size of the alloy particles, so that various specifications of powder products can be produced. While suppressing the influence of the powder preparation process on the alloy organization performance, the powder preparation energy consumption is reduced, and the preparation cost is reduced. The technical problem of the low actual discharge capacity and the kinetic performance of the existing nickel-hydrogen battery is solved. The solid solution hydrogen storage alloy uses low-cost vanadium-iron alloy as raw material, but it is a preparation method of vanadium-based hydrogen storage alloy, and the research on vanadium-chromium precursor hydrogen storage material is still in the initial stage.

[0004] The strong affinity of vanadium and hydrogen easily leads to the generation of stable hydride from excess vanadium, which hinders the release of hydrogen gas; the preparation process is complex and has high cost. SUMMARY

[0005] Therefore, the present application provides a vanadium-chromium precursor alloy for hydrogen storage and a preparation method thereof. The production cost of the hydrogen storage alloy is reduced, which is conducive to the popularization and application of the vanadium-based hydrogen storage alloy, and has important significance for forming a new vanadium-based hydrogen storage material industry and promoting the development of the hydrogen energy industry.

[0006] In order to achieve the above purpose, the present application provides a vanadium-chromium precursor alloy for hydrogen storage and a preparation method thereof, which comprises the following steps: Mixing vanadium pentoxide, chromium sesquioxide, aluminum particles and a slagging agent to obtain mixed furnace charge; Placing the mixed furnace charge into a pre-smelted furnace body, igniting and smelting, and electric refining to obtain an alloy cake; Placing the alloy cake into a water tank for water quenching, soaking for a preset time, and then crushing and screening to obtain a vanadium-chromium precursor alloy.

[0007] In some embodiments, the grade of vanadium pentoxide is ≥98.5%, the grade of chromium sesquioxide is ≥99.5%, and the purity of aluminum particles is ≥99.5%.

[0008] In some embodiments, the vanadium pentoxide has a bulk size range of <5mm, the aluminum powder has a particle size range of ≤2mm, and the chromium trioxide has a particle size range of ≤2mm.

[0009] In some embodiments, the step of placing the mixed furnace charge into a pre-smelted furnace body for ignition smelting and electro-refining to obtain an alloy cake includes: The mixed furnace charge is placed into the furnace body to be pre-smelted, and ignition material is laid on the upper surface of the mixed furnace charge for ignition smelting, producing slag and alloy liquid. A three-phase electric arc furnace is powered on to settle alloy particles in the molten slag and then discharge the slag. Vanadium pentoxide was added to the furnace body and then heated by electricity. The alloy particles are incorporated into the molten alloy and then cooled to obtain an alloy cake.

[0010] In some embodiments, when the three-phase electric arc furnace is powered on for ≥10 min, the O content in the alloy melt is ≤0.5%; When the aluminum content in the alloy liquid is ≤0.3%, the heating should be stopped.

[0011] In some embodiments, 70-80% of the total molten slag is discharged, and the remaining molten slag forms a protective layer 50-150 mm thick.

[0012] In some embodiments, the initial water quenching temperature of the alloy cake is ≥500℃, and the preset soaking time is not less than 2 hours.

[0013] In some embodiments, the crushing and screening process to obtain the vanadium-chromium precursor alloy includes: Remove slag from the alloy surface, sandblast, crush and screen to remove alloy particles with oxide film, and obtain the finished vanadium-chromium precursor alloy.

[0014] This invention proposes a vanadium-chromium precursor alloy for hydrogen storage. The mass percentage range of each component in the vanadium-chromium precursor alloy is as follows: V: 71.8%-71.9%, Al: 0.2%-0.22%, Cr: 27.3%-27.4%, Si: 0.20%-0.25%, C: 0.03%-0.04%, O: 0.29%-0.36%, with the remainder being iron.

[0015] In some embodiments, the atomic percentage of the vanadium-chromium component is 72 at%:28 at%.

[0016] The present invention has at least the following beneficial technical effects: This invention proposes a vanadium-chromium precursor alloy for hydrogen storage and its preparation method, the method comprising: mixing vanadium pentoxide, chromium trioxide, aluminum granules and slagging agent to obtain a mixed furnace charge; The mixed furnace charge is placed into a pre-smelted furnace body for ignition smelting and electric refining to obtain an alloy cake; The alloy cake was placed in a water tank for water quenching and soaked for a preset time before being crushed and screened to obtain the vanadium-chromium precursor alloy.

[0017] This invention, through in-depth optimization of the aluminothermic reduction formula and process, directly prepares high-quality vanadium-chromium alloys from oxides. This not only effectively reduces the oxygen content and impurity levels in the alloy, significantly improving its purity, but also enables precise control of the vanadium-chromium composition, meeting the requirements for subsequent hydrogen storage alloy synthesis. The rich slag generated after refining can be returned to the process flow for reuse, greatly improving resource utilization and reducing production costs. Attached Figure Description

[0018] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings: Figure 1 A flowchart of a method for preparing a vanadium-chromium precursor alloy for hydrogen storage according to the present invention is shown.

[0019] Figure 2 A flowchart of a method for preparing a vanadium-chromium precursor alloy for hydrogen storage according to an embodiment of the present invention is shown.

[0020] Figure 3 A simplified diagram of a smelting apparatus according to an embodiment of the present invention is shown. Detailed Implementation

[0021] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0022] Furthermore, the reference to "embodiment" herein means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0023] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the same meaning as in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined as in the embodiments of this application.

[0024] Please see Figure 1 This invention proposes a vanadium-chromium precursor alloy for hydrogen storage and its preparation method, comprising the following steps: Vanadium pentoxide, chromium trioxide, aluminum granules and slagging agent are mixed to obtain mixed furnace charge; The mixed furnace charge is placed into a pre-smelted furnace body for ignition smelting and electric refining to obtain an alloy cake; The alloy cake was placed in a water tank for water quenching and soaked for a preset time before being crushed and screened to obtain the vanadium-chromium precursor alloy.

[0025] The present invention aims to provide a vanadium-chromium binary material for preparing hydrogen storage alloys. This material is mainly composed of vanadium, which controls hydrogen absorption, and chromium, which controls the reversibility of hydrogen absorption and desorption. Specifically, it relates to a method for preparing a vanadium-chromium (V-Cr) alloy—a precursor material for producing hydrogen storage alloys—and particularly to a process for directly preparing the vanadium-chromium alloy from vanadium oxide (V₂O₅) and chromium oxide (Cr₂O₃) via aluminothermic reduction. This alloy can serve as a precursor material for high-performance hydrogen storage alloys (such as V-Cr-Ti, V-Cr-Fe, etc.).

[0026] This invention optimizes the aluminothermic reduction formula and process to directly prepare low-oxygen, low-impurity (O < 0.5 wt%, Al < 0.3 wt%) vanadium-chromium alloys from oxides. It achieves precise control of the vanadium-chromium composition (e.g., V:Cr = 72 at%: 28 at%), meeting the requirements for subsequent hydrogen storage alloy synthesis. The refined slag can be recycled.

[0027] In some embodiments, the vanadium pentoxide has a grade range of ≥98.5%, the chromium trioxide has a grade range of ≥99.5%, and the aluminum particles have a purity range of ≥99.5%.

[0028] In the aluminothermic reduction reaction, high-purity vanadium pentoxide and chromium trioxide can reduce side reactions caused by impurities, making the formation of the target product, vanadium-chromium alloy, more efficient and increasing the yield. Simultaneously, high-purity aluminum particles provide a more sufficient reducing agent, ensuring the complete reduction of the oxides and allowing the reaction to proceed according to the ideal stoichiometric ratio.

[0029] Low impurity content avoids introducing unnecessary elements into the alloy, ensuring that the vanadium-chromium alloy has the characteristics of low oxygen and low impurities, enabling precise control of the vanadium-chromium composition, meeting the strict requirements of raw material purity and composition for subsequent hydrogen storage alloy synthesis, and improving the performance and stability of the hydrogen storage alloy.

[0030] Using high-purity raw materials can reduce process fluctuations caused by impurities, making the aluminothermic reduction process more stable and controllable, and reducing scrap and defect rates during production. Furthermore, high-quality raw materials can reduce the burden on subsequent refining processes, lowering energy consumption and production costs. Additionally, the refined slag can be better recycled, further improving resource utilization.

[0031] In some embodiments, the vanadium pentoxide has a bulk size range of <5mm, the aluminum powder has a particle size range of ≤2mm, and the chromium trioxide has a particle size range of ≤2mm.

[0032] Smaller raw material particle sizes significantly increase the contact area between reactants. The smaller vanadium pentoxide particle size, along with the finer particle size of aluminum powder and chromium trioxide, allows for more uniform dispersion during mixing. This greatly increases the probability of collisions between reactant molecules, accelerating the aluminothermic reduction reaction and enabling it to complete in a shorter time, thus improving production efficiency. It also avoids uneven reaction caused by localized overheating or undercooling. Vanadium pentoxide, aluminum powder, and chromium trioxide participate in the reaction more thoroughly, reducing unreacted material residue, improving raw material utilization, and lowering production costs. Furthermore, the complete reaction ensures a more uniform composition and more stable quality of the resulting vanadium-chromium alloy.

[0033] In some embodiments, the step of placing the mixed furnace charge into a pre-smelted furnace body for ignition smelting and electro-refining to obtain an alloy cake includes: The mixed furnace charge is placed into the furnace body to be pre-smelted, and ignition material is laid on the upper surface of the mixed furnace charge for ignition smelting, producing slag and alloy liquid. A three-phase electric arc furnace is powered on to settle alloy particles in the molten slag and then discharge the slag. Vanadium pentoxide was added to the furnace body and then heated by electricity. The alloy particles are incorporated into the molten alloy and then cooled to obtain an alloy cake.

[0034] Laying ignition charge on the surface of the mixed furnace charge for ignition and smelting ensures a more uniform heat distribution in the initial reaction stage, allowing all parts of the mixed furnace charge to participate in the reaction simultaneously and fully. Using a three-phase electric arc furnace for refining allows the arc heat to reach a higher temperature in the molten slag, enhancing its ability to adsorb impurities. Settling alloy particles in the molten slag and discharging it effectively removes oxides and other impurities from the alloy liquid, improving alloy purity. Settling alloy particles in the molten slag and reintegrating them into the alloy liquid avoids waste of alloy resources and improves raw material utilization. Adding vanadium pentoxide to the furnace body for composition adjustment allows for flexible use of raw materials according to actual production needs, further optimizing resource allocation and reducing production costs.

[0035] In some embodiments, when the three-phase electric arc furnace is powered on for ≥10 min, the O content in the alloy melt is ≤0.5%; When the aluminum content in the alloy liquid is ≤0.3%, the heating should be stopped.

[0036] During electrorefining, the high-temperature environment generated by the continuous electric arc heating puts the molten alloy in a state of intense physical and chemical motion. A sufficiently long energizing time ensures full contact between the slag and the molten alloy. The oxides in the slag react with the oxygen in the molten alloy, forming more stable compounds that float to the top of the slag and are discharged, effectively reducing the oxygen content in the molten alloy. Alloys with low oxygen content have better toughness and plasticity, reducing defects such as cracks and brittle fractures during subsequent processing and use, thus improving the overall quality of the alloy.

[0037] Aluminum is an important alloying element in vanadium-chromium alloys, but excessive content can negatively impact alloy performance. During electric heating, the high temperature of the electric arc allows aluminum in the molten alloy to react and diffuse appropriately with other elements. Overheating not only increases energy consumption and production costs but can also lead to the volatilization and loss of elements in the molten alloy, altering the alloy's composition. Furthermore, prolonged high-temperature heating accelerates wear and tear on equipment such as the furnace and electrodes, shortening their lifespan.

[0038] In some embodiments, 70-80% of the total molten slag is discharged, and the remaining molten slag forms a protective layer 50-150 mm thick.

[0039] The slag forms a protective layer, further preventing external impurities from entering the molten alloy, avoiding secondary contamination, and ensuring the purity and quality of the alloy. During the removal of some slag, the molten alloy experiences some flow and agitation, which helps to uniformly diffuse the various elements within the alloy. The presence of the protective layer stabilizes the temperature and composition distribution of the molten alloy, reducing segregation caused by localized temperature changes or compositional fluctuations, resulting in a more uniform alloy cake composition that meets the requirements for precise raw material composition in hydrogen storage alloys.

[0040] The aluminothermic reduction reaction is intense, generating a large amount of heat and gas, which can cause molten alloy and slag to splash. A thick protective layer acts as a buffer and barrier, reducing the range and force of the splashing of molten alloy and slag.

[0041] In some embodiments, the initial water quenching temperature of the alloy cake is ≥500℃, and the preset soaking time is not less than 2 hours.

[0042] The significant temperature difference between the high-temperature alloy cake and the low-temperature water creates a powerful cooling effect. This prevents atoms in the alloy from fully diffusing and forming coarse grains, thus inhibiting grain growth and refining the alloy's grain structure. Alloys with fine-grained structures typically exhibit higher strength, hardness, and better toughness.

[0043] In actual production, various factors cause fluctuations in parameters such as the furnace exit temperature and smelting time of the alloy cake. A high initial temperature and sufficient soaking time ensure that the water quenching effect is not significantly affected. Even if the initial temperature of the alloy cake varies slightly, as long as it is within the range of ≥500℃ and the soaking time is sufficient, a relatively ideal microstructure and properties can still be obtained.

[0044] In some embodiments, the crushing and screening process to obtain the vanadium-chromium precursor alloy includes: Remove slag from the alloy surface, sandblast, crush and screen to remove alloy particles with oxide film, and obtain the finished vanadium-chromium precursor alloy.

[0045] During the smelting and cooling processes of alloys, impurities such as slag and oxides can adhere to their surfaces. Removing these surface slags effectively reduces the interference of impurities on the alloy's properties, improving the quality of vanadium-chromium precursor alloys and making them more compliant with high-purity alloy standards. During crushing and screening, the oxide film on alloy particles may break down and become embedded within the alloy, forming micro-defects. These defects can become crack initiation points when the alloy is subjected to external forces or specific environmental conditions, leading to a decrease in the alloy's strength and toughness. Removing these particles reduces the formation of internal defects and improves the alloy's mechanical properties.

[0046] This invention proposes a vanadium-chromium precursor alloy for hydrogen storage. The mass percentage range of each component in the vanadium-chromium precursor alloy is as follows: V: 71.8%-71.9%, Al: 0.2%-0.22%, Cr: 27.3%-27.4%, Si: 0.20%-0.25%, C: 0.03%-0.04%, O: 0.29%-0.36%, with the remainder being iron.

[0047] Vanadium-based alloys possess high hydrogen storage capacity, capable of storing a significant amount of hydrogen per unit volume or mass. Under appropriate conditions, vanadium-based alloys exhibit rapid hydrogen absorption and release kinetics, enabling the storage and release of hydrogen in a short time, meeting the rapid response requirements of practical applications. Compared to high-pressure gaseous hydrogen storage and cryogenic liquid hydrogen storage, vanadium-based alloys utilize solid-state hydrogen storage, eliminating the stringent requirements of high pressure and low temperature, thus reducing the risk of hydrogen leakage, explosions, and other hazards, resulting in higher safety. After multiple hydrogen absorption and release cycles, vanadium-based solid-state hydrogen storage materials maintain good hydrogen storage performance, exhibiting a long service life and high stability, making them suitable for long-term, repeated use.

[0048] In some embodiments, the atomic percentage of the vanadium-chromium component is 72:28 at%.

[0049] Please see Figure 2 and Figure 3 The specific process flow of this invention is as follows: like Figure 2 As shown, the furnace charge preparation involves selecting aluminum powder with a grade ≥98.5% V₂O₅, ≥99.5% Cr₂O₃, and a purity ≥99.5%, along with slagging agents, and mixing them thoroughly in a specific ratio. The V₂O₅ particle size must be <5mm, the aluminum powder particle size ≤2mm, and the Cr₂O₃ particle size ≤2mm. Using smaller particle sizes ensures accurate charge preparation, uniform mixing, and a stable and rapid reaction, achieving 100% reaction completion, thus yielding an alloy with minimal compositional fluctuations. Using purer raw materials minimizes impurities introduced into the product, improving product purity.

[0050] Furnace body preparation: The smelting furnace body serves as a steel composite outer shell, with a 100-150mm permanent corundum layer poured or built inside; the permanent layer is filled with a 100-150mm working layer, which consists of two layers: an outer layer of 50-80mm filled with crushed alloy smelting slag powder ≤10mm; and an inner working layer in contact with the alloy, made of <1mm fused corundum powder or fused magnesia powder with a purity of 99.0% or higher. The working layer is fixed with a mold made of aluminum foil or sheet metal, and placed on a vibrating table to compact for more than 20 minutes to make the working layer dense and compact, minimizing residual air in the working layer; alternatively, the working layer can also be made by tamping fused corundum or magnesia with a binder, then baking and sintering.

[0051] Alloy smelting: The prepared furnace charge is added into the furnace body, the material inside the furnace is leveled, and ignition material is laid on the upper surface and ignited. The furnace charge reacts rapidly and violently, and all the furnace charge is generally reacted within 60 seconds. The high temperature generated by the smelting reaction quickly sinterstals the inner surface of the working layer into a dense thin layer. The slag and alloy liquid produced by smelting are separated in the furnace. The alloy liquid settles at the bottom of the furnace body, and the slag gathers on top of the alloy. The alloy liquid is protected by the sintered furnace lining material and the slag of the smelting parameters, avoiding oxidation contamination of the alloy by the outside air. After the smelting reaction is completed, the slag and alloy liquid produced by smelting are energized in the furnace using a three-phase electric arc furnace. The slag temperature is maintained above 1600℃, and the energizing time is ≥10min. This allows the alloy particles in the slag to settle fully, ensuring that the alloy particles in the slag settle fully and that the residual O in the alloy liquid is removed. This ensures that the O content in the alloy liquid is ≤0.5%, thereby improving the metal recovery rate and alloy quality. Alloy refining: Approximately 70-80% of the total slag is discharged from the furnace, leaving a 50-150 mm layer of slag on top of the molten alloy as a protective layer to prevent oxidation upon contact with air. V₂O₅ (or Cr₂O₃) is added to the furnace and heated to remove Al from the molten alloy. Refining is complete when the Al content in the molten alloy is ≤0.3%.

[0052] Static cooling and furnace dismantling water quenching: After the alloy liquid and slag are cooled in the furnace for 16 hours, the furnace is dismantled, the alloy and slag are separated, and the red-hot alloy cake is placed in a water tank or sprayed with cold water. The initial water quenching temperature of the alloy cake is ≥500℃ to ensure a good water quenching effect, increase the brittleness of the alloy, and facilitate the crushing and processing of the alloy cake.

[0053] Product processing: After separation and cleaning, the alloy cake is cleaned to remove the slag on the alloy surface, then sandblasted to remove the surface oxide film, crushed into pieces of suitable size, crushed by a crusher and screening system to obtain the particle size required by the user, and then sorted manually or by machine to remove the alloy particles with residual oxide film. Finally, it is weighed and packaged to become a vanadium-chromium finished product that can be used to smelt hydrogen storage alloys.

[0054] Figure 3 The diagram shows a smelting apparatus. Three probes, labeled A, B, and C, are connected to the electrical control system on the right via wires. These probes are used to monitor various parameters of the smelting solution in real time, such as temperature, component concentration, and pH. The electrical control system is connected to a transformer below, which regulates the voltage to meet the power requirements of the control system or the entire system. The probes are mounted on a robotic arm structure, which adjusts the probe position to ensure accurate immersion in the liquid for detection. The movement of the robotic arm is controlled by the electrical control system.

[0055] Example 1 (1) 1000 kg of 99.2% flake vanadium pentoxide (particle size ≤ 5 mm), 300 kg of 99.7% pure Cr2O3, 559 kg of 99.7% metallurgical aluminum powder (< 2 mm), and 120 kg of slag-forming agent were accurately added and then thoroughly mixed in a mixer for 9 min.

[0056] (2) Prepare the smelting furnace body according to the requirements of step (2), and ensure that the refractory materials of the permanent layer and working layer of the furnace body are dried. The thickness of the permanent layer + working layer is 260mm. (3) Prepare the furnace charge and put it into the smelting furnace. Lay the ignition material and transport it into the smelting reaction chamber. Ignite and smelt. After the reaction is completed, turn on the electric arc furnace for 10 minutes. Then, discharge 1000 kg of molten slag from the furnace. Then, add 100 kg of V2O5 to the molten pool and turn on the electric arc furnace for refining. After refining for 30 minutes, turn off the power to end the refining. Let the furnace stand for 30 minutes. Then, lift it to the cooling site and let it cool naturally for 20 hours. After that, dismantle the furnace and separate the slag and alloy. After dismantling the furnace, the surface temperature of the alloy cake is 620℃. (4) Place the red-hot alloy cake into a water tank for water quenching. The water temperature of the alloy cake is 560℃. After soaking for 2 hours, take it out. (5) The alloy is finished, sandblasted, crushed and screened, and then manually sorted and packaged to obtain 572 kg of well-crystallized, bright, pore-free, slag-free and easily broken alloy.

[0057] (6) The vanadium-chromium precursor alloy composition of the sample was as follows: V=71.8%, Al=0.22%, Cr=27.4%, Si=0.20%, C=0.03%, O=0.36%.

[0058] Example 2 (1) 1000 kg of 99.5% flake vanadium pentoxide (particle size ≤ 5 mm), 300 kg of 99.7% pure Cr2O3, 549 kg of 99.7% metallurgical aluminum powder (< 2 mm), and 120 kg of slag-forming agent were accurately added and then thoroughly mixed in a mixer for 9 min.

[0059] (2) Prepare the smelting furnace body according to the requirements of step (2), and ensure that the refractory materials of the permanent layer and working layer of the furnace body are dried. The thickness of the permanent layer + working layer is 260mm. (3) Prepare the furnace charge and put it into the smelting furnace. Lay the ignition material and transport it into the smelting reaction chamber. Ignite and smelt. After the reaction is completed, turn on the electric arc furnace for 10 minutes. Then, discharge 1100 kg of molten slag from the furnace. Then, add 120 kg of Cr2O3 to the molten pool and turn on the electric arc furnace for refining. After refining for 30 minutes, turn off the power to end the refining. Let the furnace stand for 30 minutes. Then, lift it to the cooling site and let it cool naturally for 21 hours. After that, dismantle the furnace and separate the slag and alloy. After dismantling the furnace, the surface temperature of the alloy cake is 600℃. (4) Place the red-hot alloy cake into a water tank for water quenching. The water temperature of the alloy cake is 550℃. After soaking for 2 hours, take it out. (5) The alloy is finished, sandblasted, crushed and screened, and then manually sorted and packaged to obtain 708 kg of well-crystallized, bright, pore-free, slag-free and easily broken alloy.

[0060] (6) The vanadium-chromium precursor alloy composition of the sample was as follows: V=71.9%, Al=0.2%, Cr=27.3%, Si=0.25%, C=0.03%, O=0.29%.

[0061] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0062] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable way without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0063] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A method for preparing a vanadium-chromium precursor alloy for hydrogen storage, characterized in that, Includes the following steps: Vanadium pentoxide, chromium trioxide, aluminum granules, and slagging agent are mixed to obtain a mixed furnace charge; The mixed furnace charge is placed into a pre-smelted furnace body for ignition smelting and electric refining to obtain an alloy cake; The alloy cake was placed in a water tank for water quenching and soaked for a preset time before being crushed and screened to obtain the vanadium-chromium precursor alloy.

2. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 1, characterized in that, The vanadium pentoxide has a grade range of ≥98.5%, the chromium trioxide has a grade range of ≥99.5%, and the aluminum particles have a purity range of ≥99.5%.

3. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 1, characterized in that, The vanadium pentoxide has a bulk size range of <5mm, the aluminum powder has a particle size range of ≤2mm, and the chromium trioxide has a particle size range of ≤2mm.

4. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 1, characterized in that, The step of placing the mixed furnace charge into a pre-smelted furnace body for ignition smelting and electric refining to obtain an alloy cake includes: The mixed furnace charge is placed into the furnace body to be pre-smelted, and ignition material is laid on the upper surface of the mixed furnace charge for ignition smelting, producing slag and alloy liquid. A three-phase electric arc furnace is powered on to settle alloy particles in the molten slag and then discharge the slag. Vanadium pentoxide was added to the furnace body and then heated by electricity. The alloy particles are incorporated into the molten alloy and then cooled to obtain an alloy cake.

5. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 4, characterized in that, When the three-phase electric arc furnace is powered on for ≥10 min, the oxygen content in the alloy liquid is ≤0.5%; When the aluminum content in the alloy liquid is ≤0.3%, the heating should be stopped.

6. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 4, characterized in that, 70-80% of the total molten slag is discharged, and the remaining molten slag forms a protective layer 50-150mm thick.

7. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 1, characterized in that, The initial water quenching temperature range for the alloy cake is ≥500℃, and the preset immersion time is not less than 2 hours.

8. The method for preparing vanadium-chromium precursor alloy for hydrogen storage according to claim 1, characterized in that, The crushing and screening process yields vanadium-chromium precursor alloys, including: Remove slag from the alloy surface, sandblast, crush and screen to remove alloy particles with oxide film, and obtain the finished vanadium-chromium precursor alloy.

9. A vanadium-chromium precursor alloy for hydrogen storage, characterized in that, The mass percentage range of each component in the vanadium-chromium precursor alloy is as follows: V: 71.8%-71.9%, Al: 0.2%-0.22%, Cr: 27.3%-27.4%, Si: 0.20%-0.25%, C: 0.03%-0.04%, O: 0.29%-0.36%, with the remainder being iron.

10. The vanadium-chromium precursor alloy for hydrogen storage according to claim 9, characterized in that, The atomic percentage of the vanadium-chromium component is 72 at%: 28 at%.